A new approach in compatibilization of the poly(lactic acid)/thermoplastic starch (PLA/TPS) blends. (25th June 2016) - Akrami, Marzieh; Ghasemi, Ismaeil; Azizi, Hamed; Karrabi, Mohammad; Seyedabadi, Mohammad
Highlights: Synthesis of a new compatibilizer for PLA/TPS blends. The designed structure of the compatibilizer is able to increases interfacial adhesion. Characterization of compatibilizer using appropriate methods. Checking the efficiency of compatibilizer via monitoring of the different properties of PLA/TPS blends. Abstract: In this study, a new compatibilizer was synthesized to improve the compatibility of the poly(lactic acid)/thermoplastic starch blends. The compatibilizer was based on maleic anhydride grafted polyethylene glycol grafted starch (mPEG-g-St), and was characterized using Fourier transform infrared spectroscopy (FTIR), dynamic mechanical thermal analysis (DMTA) and back titration techniques. The results indicated successful accomplishment of the designed reactions and formation of a starch cored structure with many connections to m-PEG chains. To assess the performance of synthesized compatibilizer, several PLA/TPS blends were prepared using an internal mixer. Consequently, their morphology, dynamic-mechanical behavior, crystallization and mechanical properties were studied. The compatibilizer enhanced interfacial adhesion, possibly due to interaction between free end carboxylic acid groups of compatibilizer and active groups of TPS and PLA phases. In addition, biodegradability of the samples was evaluated by various methods consisting of weight loss, FTIR-ATR analysis and morphology. The results revealed no considerable effect of compatibilizer on biodegradability of samples.